2020
DOI: 10.3892/or.2020.7674
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of PI3K110α as a novel therapeutic strategy for cetuximab‑resistant oral squamous cell carcinoma

Abstract: High expression of the 110 kDa catalytic subunit of the class IA PI3K (PI3Kp110α) may play an important role in cetuximab resistance exhibited by both colorectal cancer and head and neck squamous cell carcinoma. Therefore, the present study aimed to examine the association between the expression of proteins in the PI3Kp110α pathway and cetuximab resistance, and the antitumor effects of alpelisib (PI3K inhibitor) and cetuximab in oral squamous cell carcinoma (OSCC) cells. The association between PI3Kp110α prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…We describe our experiences of three patients who received Cmab in combination with RT (Cmab + RT) for loco-regional recurrent OSCC and achieved long-term survival of 5 years or more while maintaining the QOL. We also reported PI3Kp110α findings from an immunohistochemical study to clarify the validity of our previous report (7).…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…We describe our experiences of three patients who received Cmab in combination with RT (Cmab + RT) for loco-regional recurrent OSCC and achieved long-term survival of 5 years or more while maintaining the QOL. We also reported PI3Kp110α findings from an immunohistochemical study to clarify the validity of our previous report (7).…”
Section: Introductionmentioning
confidence: 60%
“…Immunohistochemical staining was performed by using the EnVision method (EnVision+; Dako), as previously described (7). For the assay, specimens were obtained immediately before Cmab + RT.…”
Section: Im M U N Oh Isto Ch E M Ic a L Sta I N I Ng A N D E Va Lu A ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted on OSCC cells and xenograft model, it became evident that the abrogation of p110α catalytic subunit of PI3K using alpelisib significantly enhanced the sensitivity of the cells to cetuximab 188 . It has been also suggested that the blockage of the PI3K/Akt signaling axis may diminish the expression level of an epithelial‐mesenchymal transition‐related protein N‐cadherin, suggesting that PI3K inhibitor may reinforce the anti‐cancer property of cetuximab through suppression of cell invasion 189 . In another study, the combination of cetuximab with pan PI3K inhibitor LY294002 resulted in enhanced cytotoxicity 188 .…”
Section: Pi3k Inhibitors: An Opportunity For the Treatment Of Hnsccmentioning
confidence: 99%
“…BYL719 is orally available, and in the majority of rodent studies it is administered via a once-daily oral gavage or i.p. injection [ 19 , 20 ]. However, this is not feasible for long-term aging or metabolic disease studies where treatment time may be in excess of 1 year.…”
Section: Introductionmentioning
confidence: 99%